2024
DOI: 10.18063/ijb.v6i3.304
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-free, Label-free, and Nozzle-free Magnetic Levitational Bioassembler for Rapid Formative Biofabrication of 3D Tissues and Organs

Abstract: Scaffolding is the conceptual framework of conventional tissue engineering. Over the past decade, scaffold-free approaches as a potential alternative to classic scaffold-based methods have emerged, and scaffold-free magnetic levitational tissue engineering (magnetic force-based tissue engineering [Mag-TE]) is a type of this novel tissue engineering strategy. However, Mag-TE is often based on the use of potentially toxic magnetic nanoparticles. Scaffold-free and label-free magnetic levitational bioassembly do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In a recent study conducted at the International Space Station, undesirable cytotoxic effects of the particles were reduced by using low-toxicity Gd 3+ salts and performing the assembly in microgravity. The latter was successfully reported by Parfenov et al (2020) in constructing 3D cartilage tissue incorporating human chondrocytes. The fusion of chondrospheres was observed in a non-toxic paramagnetic Gd 3+ cell culture medium overcoming the gravitational force constraint [31].…”
Section: Magnetic Assisted Assemblymentioning
confidence: 79%
See 2 more Smart Citations
“…In a recent study conducted at the International Space Station, undesirable cytotoxic effects of the particles were reduced by using low-toxicity Gd 3+ salts and performing the assembly in microgravity. The latter was successfully reported by Parfenov et al (2020) in constructing 3D cartilage tissue incorporating human chondrocytes. The fusion of chondrospheres was observed in a non-toxic paramagnetic Gd 3+ cell culture medium overcoming the gravitational force constraint [31].…”
Section: Magnetic Assisted Assemblymentioning
confidence: 79%
“…successfully reported by Parfenov et al (2020) in constructing 3D cartilage tissue incorporating human chondrocytes. The fusion of chondrospheres was observed in a non-toxic paramagnetic Gd 3+ cell culture medium overcoming the gravitational force constraint [28].…”
Section: Magnetic Assisted Assemblymentioning
confidence: 94%
See 1 more Smart Citation
“…For a magnetic levitational bioassembly process at ISS, Parfenov et al have already shown that a cell-protective transport of living tissue spheroids embedded in a thermoreversible hydrogel is possible to bring them safely and vital to the station. [59] Even if it is unlikely due to the trouble-free centrifugation without loss of function of the hydrogels in the lab, it remains also to be seen how the general influence of vibrations and acceleration during the rocket launch on the bioinks is. It also still has to be observed whether microgravity could possibly also have an influence on the cold-stored cells, which would require adjustments in the storage process.…”
Section: Discussionmentioning
confidence: 99%
“…Gadolinium is a rare-earth element widely applied in medical applications being included into complex chemical substances. Parfenov et al demonstrated that supplementation of the liquid medium with another gadolinium-based substance, gadobutrol ([10-[2,3-dihydroxi-1-(hydroxymethyl)propil]-1,4,7,10-tetraazacyclododexan-1,4,7-triacetin(3-)-N1, N4, N7, N10,O1, O4, O7]gadolinium), taken in concentration of 10 mM provides levitation of human cells in the static magnetic field created with the NdFeB magnets with a remnant magnetization of 1.21 T [59,60]. Similar conditions allowed for magnetic levitation of bacterial cells [52].…”
Section: Maglev Systems Based On Permanent Magnetsmentioning
confidence: 99%